Anatomical study of the innervation of different parts of the posterior ligamentous region of the sacroiliac joint. Issue 5 (22nd February 2021) - Zhu, Weijia; Zhao, Qinghao; Ma, Runxun; Liu, Zezheng; Zhao, Jianjun; Liu, Zexian; Chen, Junjie; Zhang, Rusen; Zheng, Zhiyang; Xu, Yejie; Deng, Shangxi; Cheng, Liang; et al.
Abstract : Background and objectives: The periarticular sacroiliac joint (SIJ) technique has become an important area of focus, and the quartering of the SIJ posterior ligamentous region has been proposed as a way to refine this technique. However, detailed nerve distribution combined with the division of the SIJ posterior ligamentous region is lacking. We aimed to explore the innervation of the SIJ posteriorly based on the quartering of the SIJ posterior ligamentous region. Methods: Sixteen SIJs from eight embalmed cadavers were studied. Each SIJ posterior ligamentous region was equally divided into areas 0–3 from top to bottom. The origin, distribution, quantity, transverse diameter, spatial orientation, relation with bony structures, and the number of identifiable terminal nerve branches in each area were examined. Results: Areas 0–1 were innervated by the lateral branches of the dorsal rami of L4−L5 directly in all specimens. Areas 2–3 were innervated by that of both lumbar and sacral nerves via the posterior sacral network (PSN), with L5 contributing to the PSN in all specimens and L4 in 68.75%. The number of identifiable terminal nerve branches were significantly higher in areas 2–3 than in areas 0–1. Conclusions: The inferior part of the SIJ posterior ligamentous region seems to be the main source of SIJ-related pain and is innervated by lumbar and sacral nerves via the PSN. However, the superior part directly innervated by lumbar nerves should not be neglected, and further clinical verification is needed.